PERANAN KELOMPOK WANITA TANI SEKAR KANTIL DALAM MENINGKATKAN EKONOMI MASYARAKAT DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Santosa, Mustika Edi (EKSYDA: Jurnal Studi Ekonomi Syariah, 2022)
The availability of resources in the village is an important factor in improving the economy of the village community. Thus, there is a need for wise management of these resources in order to create effectiveness and efficiency in their use. This can be achieved through community empowerment, particularly through the role of the Women Farmers Group (KWT). The purpose of this study was to determine the role of KWT Sekar Kantil in improving the economy of the community in Astomulyo Village, Punggur District, Central Lampung Regency. This type of research is a descriptive field research. In the technique of determining informants, the researcher uses a proposive sampling technique. Meanwhile, in collecting data using interview and documentation techniques, which were then analyzed qualitatively with an inductive framework of thinking. The results of this study indicate that the role of KWT Sekar Kantil in improving the economy of the community in Astomulyo Village includes providing new jobs for the community, increasing community income, creating convenience for the community in meeting their daily needs, creating a fair distribution of income, and creating changes in the economic structure. people from previously working as farmers or ranchers, are now starting to enter the business sector or home industry.